PENGARUH PENERAPAN MODEL COOPERATIVE LEARNING BERBANTUAN MEDIA SCARBBLE DALAM MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA INGGRIS SISWA KELAS IV DI SDN 2 KOTA AGUNG KABUPATEN LAHAT - Sumantri, Suci; Nurlaila; Fatimah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Scrabble-assisted cooperative learning model on improving the English vocabulary skills of fourth-grade students at SDN 2 Kota Agung. The research method used is quantitative research, with a pre-experimental design in the form of a one-group pre-test-post-test design. The data analysis techniques used were normality tests and hypothesis testing using the Wilcoxon formula. The population and sample were fourth-grade students, totaling 21 students. The data collection techniques used in this study were observation, testing, and documentation. This research was assisted by the SPSS Statistics 21 for Windows program. The results of this study showed that the average learning outcome at the pre-test was 51.62, while the average score at the post-test was 85.14. These results showed an increase in student learning outcomes of 33.52. It is known that sig (2-tailed) is 0.000 < 0.05, so it can be seen from the calculation results that Ho is rejected and Ha is accepted. Therefore, it can be concluded based on significance that the cooperative learning model assisted by Scrabble media can improve the English vocabulary skills of fourth-grade students at SDN 2 Kota Agung, Lahat Regency.